A new jumping spider of the genus Stenaelurillus Simon, 1886 from India (Araneae: Salticidae: Aelurillina) - Caleb, John T.d.; Mathai, Manu Thomas (Zootaxa, 2016)
The genus Stenaelurillus Simon, 1886 is known from 35 species worldwide, including 27 species from Africa and eight from Asia (four species known from India, one from Iran, one from China, one from Tibet and one from Vietnam) (World Spider Catalog 2016). The four species known from India are S. albus Sebastian et al., 2015, S. jagannathae Das, Malik & Vidhel, 2015, S. lesserti Reimoser, 1934 and S. sarojinae Caleb & Mathai, 2014 (Prószyński 2015; World Spider Catalog 2016). The present paper contains description of Stenaelurillus metallicus sp. nov., discovered from scrub jungle remnants of tropical dry evergreen forests, a unique habitat found in Madras Christian College campus, Chennai, Tamil Nadu, India.